2016
DOI: 10.1007/s10565-016-9350-0
|View full text |Cite
|
Sign up to set email alerts
|

New biomarkers and therapeutics can be discovered during COPD-lung cancer transition

Abstract: Chronic obstructive pulmonary disease (COPD) has been found to be associated with lung cancer regardless of a patient's smoking history. Of 11,888 incident cases of lung cancer, 23 % had a prior diagnosis of COPD compared with only 6 % of the 37,605 controls (Powell et al. 2013). The prevalence of COPD in lung cancer patients varies from 8 to 50 %, and the annual incidence of lung cancer arising from COPD is 0.8-1.2 %. This indicates that ∼1 % of COPD patients develop lung cancer each year, while only 0.2 % of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Further data mining showed significantly higher MEF2D level in COPD patients with NSCLC than that in smokers, patients with COPD and no NSCLC, or patients with NSCLC and no COPD. Growing evidence has shown that patients with chronic respiratory conditions such as COPD exhibit a significantly higher risk of lung cancer [8]. It is reported that 50–90% lung cancer patients have coexisting COPD [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further data mining showed significantly higher MEF2D level in COPD patients with NSCLC than that in smokers, patients with COPD and no NSCLC, or patients with NSCLC and no COPD. Growing evidence has shown that patients with chronic respiratory conditions such as COPD exhibit a significantly higher risk of lung cancer [8]. It is reported that 50–90% lung cancer patients have coexisting COPD [20].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic respiratory diseases are predisposed to higher incidence of lung cancer [27]. Chronic obstructive pulmonary disease (COPD), a chronic inflammatory lung disease, is closely related to susceptibility to lung cancer and stands as the most important risk factor of lung cancer among smokers [8]. Patients with moderate-to-severe COPD have a fivefold higher risk of developing lung cancer than smokers without the disease [9].…”
Section: Introductionmentioning
confidence: 99%
“…Another question is whether acRoots-induced down-regulation of RARB is acRoots inhibition-specific or a general reaction of the compensation, since we found that LPS could also induce the down-regulation of RARB gene. It is also critical to validate the repeatability and stability of RARB-interacted elements in metabolism-associated network as efficacy-specific biomarkers and druggable targets [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell measurements were used to evaluate the DNA-damaging ability of the herbicide in freshly isolated human leukocytes (Villarini et al 2000) or the ethoxyresorufin-Odeethylase activity of cytochrome P450 1A1 in singleliving cells with the microspectrofluorometric technique (Taira et al 2007). The measurements of single-cell biology and sequencing are recently considered as an important approach to investigate molecular mechanisms of drug efficacy and resistances, discovery and development of therapeutic targets, and genealogic phenotypes of cells during disease progression (Chu et al 2017;Wang 2016;Wang et al 2017). Single-cell sequencing is an important measure to define intercellular heterogeneity, rare cell types, cell genealogies, somatic mosaicism, microbes, and disease evolution, including single-cell DNA genome sequencing, DNA methylome sequencing, and RNA sequencing.…”
mentioning
confidence: 99%